Coumarin-Induced Delay of Rice Seed Germination Is Mediated by Suppression of Abscisic Acid Catabolism and Reactive Oxygen Species Production - Chen, Bing-Xian; Peng, Yuan-Xuan; Gao, Jia-Dong; Zhang, Qi; Liu, Qin-Jian; Fu, Hua; Liu, Jun (Frontiers in Plant Science, 2019)
Abscisic acid (ABA) is a crucial phytohormone for the regulation of seed germination. The ABA content of seeds is regulated by synthesis and catabolic pathways. Coumarin, an important plant allelochemical, can inhibit seed germination effectively, although whether it is involved in the regulation of ABA content during seed germination has not been elucidated. For the study reported herein, we show that coumarin effectively inhibits rice seed germination and vivipary. We found that the ABA content gradually decreased in water-imbibed rice seeds and that the content and activity of the Oryza sativa 9-cis epoxycarotenoid dioxygenases (OsNCEDs), which are ABA synthases, decreased during seed germination. At the transcription level, the expression of OsNCED1-3 appeared to decrease, whereas expression of the ABA 8'-hydroxylase 2 and 3 genes (OsABA8'ox2/3) first appeared to increase and then decrease. Samples of rice seeds were also imbibed in water containing coumarin, which increased their ABA content but did not significantly increase the activity or content of their OsNCEDs or OsNCED1–3 transcription. Interestingly, coumarin imbibition remarkably reduced OsABA8'ox2/3 expression in rice embryos, which partially explained how coumarin increased the ABA content of germinating rice embryos. Coumarin also inhibited the accumulation of reactive oxygen species (ROS) in rice embryos and increased the activity of superoxide dismutase and catalase, which are indispensable for seed germination. These results indicate that coumarin delays seed germination by inhibiting ABA catabolism, particularly by decreasing the expression of OsABA8'ox2/3 rather than by increasing ABA synthesis. Moreover, coumarin increases the ABA content while decreasing the ROS content in rice embryos. Our results enhance our understanding of the regulation of ABA and ROS during seed germination and provide theoretical support for application of coumarin to prevent sprouting before crop harvesting.